Genistein acts in bone metabolism and improves peri-implant healing in rats with estrogen deficiency (Research, Society and Development, 2021)
The present study aimed to evaluate the peri-implantar bone healing in the presence of genistein treatment in ovariectomized rats. Thirty female rats with 4 months old were divided into 3 groups according to the experimental condition and the drug treatment: SHAM (rats submitted to the fictional surgery and gavage with 0.9% saline solution); OVX (rats submitted to bilateral ovariectomy and gavage with 0.9% saline solution); OVX GEN (rats submitted to bilateral ovariectomy and gavage with 1mg/day of genistein). 60 implants were installed, with two implants in each animal. The calcified group was subjected microcomputerized tomography and the parameters analysed was bone volume per tissue volume (BV/TV) and connective density (Cnn.Dn). The decalcified samples were evaluated through immunolabeling analysis, in order to detect the presence of RUNX2, Alkaline Phosphatase, Osteocalcin, Osteopontin and TRAP. All the quantitative data were submitted to the normality curve to determine the most adequate test. The significance level of p